2020
DOI: 10.1007/s13300-020-00925-8
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Efficacy of Second-Generation Basal Insulin Analogues in Adults with Type 2 Diabetes at Risk of Hypoglycemia and Use in Other Special Populations: A Narrative Review

Abstract: Hypoglycemia is a major barrier impeding glycemic control in persons with type 2 diabetes mellitus and creates a substantial burden on the healthcare system. Certain populations that require special attention, such as older adults and individuals with renal impairment, a longer To view digital features for this article go to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 91 publications
(250 reference statements)
1
16
0
3
Order By: Relevance
“…In summary, the sustained glycaemic benefits of Gla-300 in the older adult population, as well as its reduced risk of hypoglycaemia compared to first-generation basal insulin analogues, support its use in older adults with T2DM. In addition, the flexibility and convenience of a once-daily injection of Gla-300 is advantageous in this population who may rely on caretakers to administer insulin [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the sustained glycaemic benefits of Gla-300 in the older adult population, as well as its reduced risk of hypoglycaemia compared to first-generation basal insulin analogues, support its use in older adults with T2DM. In addition, the flexibility and convenience of a once-daily injection of Gla-300 is advantageous in this population who may rely on caretakers to administer insulin [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the findings of the REALI CKD pooled analysis, along with the data from the aforementioned post hoc analyses [ 8 , 9 ], support the use of Gla-300 in patients with renal impairment, given its sustained glycaemic control benefit and its overall low risk of hypoglycaemia in this challenging-to-treat population that is particularly vulnerable to hypoglycaemia. This vulnerability is due to multiple factors, including a reduced renal mass and therefore a reduced capacity for renal glucose release, especially when the eGFR falls below 45 mL/min/1.73 m 2 [ 4 , 7 , 21 ]. Hypoglycaemic events affect patients’ lives profoundly, as they are associated with psychological distress, cardiovascular morbidity, and a significantly increased risk of death within 1 day of a hypoglycaemic event [ 4 , 7 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sales of insulin degludec grew 1.8-fold in 2017 vs. 2016, rising to US$1.11 billion in 2017 ( 24 ). This increase has been supported by studies demonstrating the cost-effectiveness of degludec compared with other long-acting insulin analogues ( 25 28 ).…”
Section: Introductionmentioning
confidence: 89%
“…In addition, improving patient comfort and convenience ( 62 ). Published studies have shown that Gla-300 does improve glycaemic control alongside reducing the incidence of nocturnal hypoglycaemia vs. the 100 IU/ml formulation ( 25 , 62 65 ). However, some authors and health authorities are not convinced of the benefits of Gla-300 ( 66 ), and have restricted its prescribing vs. the 100 IU/ml formulation ( 67 ).…”
Section: Introductionmentioning
confidence: 99%